A universal strategy to obtain highly redox-active porous carbons for efficient energy storage. Issue 7 (29th January 2020) - Song, Ziyang; Miao, Ling; Li, Liangchun; Zhu, Dazhang; Lv, Yaokang; Xiong, Wei; Duan, Hui; Wang, Zhiwei; Gan, Lihua; Liu, Mingxian
Abstract : A universal route based on benzoquinone and amines with different chemical structures and compositions is developed to engineer geometrically tailored, highly redox-active O/N codoped porous carbons for high-efficiency energy storage. Abstract : Quinones are highly redox-active due to their remarkable electron transfer kinetics and electrochemical reversibility, and amines credited with exceptional electron-pair donicity can strengthen the redox kinetics of quinones and simultaneously incorporate electroactive nitrogen species. Herein, a universal route based on benzoquinone and amines with different chemical structures is developed to engineer O/N codoped porous carbons. This approach drives the designability of high-surface-area carbons with tailored geometries (nanosphere, nanofiber, granule and honeycomb), ensuring fast ion/electron transport kinetics to support electrical double layer capacitance. Besides, highly redox-active O/N heteroatoms trigger remarkable pseudocapacitance via reversible faradaic reactions of benzoquinone/hydroquinone transformation and pyridinic/pyrrolic nitrogen response in a H2 SO4 electrolyte. Consequently, a representative supercapacitor achieves greatly enhanced electrochemical reaction dynamics, yielding an extraordinary energy density (18.2 W h kg −1 ), ultralong stability and excellent high-rate features (90.1% energy retention over 100 000 successive cycles at 20 A g −1 ). The enhanced wetting compatibility of carbon surfaces/electrolyte ions resulting from O/N doping can further extend the carbon electrodes to water-in-salt, organic and ionic liquid electrolytes for constructing high energy supercapacitors (up to 90.6 W h kg −1 ). This work provides a general guidance to design high-performance carbons toward efficient energy storage.